Jon Driver: a tribute. (11th June 2013) - Shallice, Tim
Abstract : Professor Jon Driver made significant contributions to cognitive neuroscience. This paper pays tribute to that work and to the personal qualities of Jon that so many of his colleagues were fortunate enough to experience.